2019
DOI: 10.1101/858811
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanistic models of signaling pathways deconvolute the functional landscape of glioblastoma at single cell resolution

Abstract: The rapid development of single cell RNA-sequencing (scRNA-seq) technologies is revealing an unexpectedly large degree of heterogeneity in gene expression levels across the different cells that compose the same tissue sample. However, little is known on the functional consequences of this heterogeneity and the contribution of individual cell-fate decisions to the collective behavior of the tissues these cells are part of. Mechanistic models of signaling pathways have already proven to be useful tools for under… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 84 publications
(87 reference statements)
0
2
0
Order By: Relevance
“…The approach presented here, based on mechanistic modeling of cell signaling pathways, shows its potential in evaluating the gender-specific differences in certain mechanisms of action of several drugs, and, therefore, in predicting potential non-responders and resistances [58,100]. It has also been shown that mechanistic models can be an excellent tool for the simulation of the effect of drugs, as we have recently demonstrated in cancer [27]. In particular, Table 4 shows circuits that display GS-DSA after the simulation of drugs for which a gender-specific activity has been reported, but never display GS-DSA in simulations of drugs with similar activity in both genders.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The approach presented here, based on mechanistic modeling of cell signaling pathways, shows its potential in evaluating the gender-specific differences in certain mechanisms of action of several drugs, and, therefore, in predicting potential non-responders and resistances [58,100]. It has also been shown that mechanistic models can be an excellent tool for the simulation of the effect of drugs, as we have recently demonstrated in cancer [27]. In particular, Table 4 shows circuits that display GS-DSA after the simulation of drugs for which a gender-specific activity has been reported, but never display GS-DSA in simulations of drugs with similar activity in both genders.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, we will use this mechanistic framework to understand what is the molecular basis of the different effects of cancer drugs by directly simulating their effect in the patients. This approach has recently been used by us to understand the generation of resistances in cancer at the single cell level in glioblastoma [27].…”
Section: Introductionmentioning
confidence: 99%